Risk of developing retinopathy of prematurity in infants varying in hematological parameters, gestational age and some treatment-related factors - S.V. Katsan; A.O. Adakhovska (Ukrainian Society of Ophthalmologists, 2018)
Background: Investigating risk factors for severe retinopathy of prematurity (ROP) is important, given the prevalence of ROP. Purpose: To determine the association of severe ROP with hematological parameters, gestational age and some treatment-related factors. Materials and Methods: The investigation involved a retrospective analysis of some hematological parameters (red blood cell (RBC), white blood cell (WBC) and platelet counts (PLC)) in 1248 preterm neonates. Hematological results were (a) abstracted from neonates' medical records kept while infants were staying in neonatal care units, and (b) compared with Children's Reference Ranges for Routine Hematology Tests at age 1 month. Statistical analyses were performed using Medstat Software version 16.8.4. Models were developed and analyzed using EZR version 1.32. Results: We found the following independent variables to be associated with an increased risk of severe ROP: low gestational age (OR, 0.52; 95% CI, 0.45 - 0.60; p < 0.001), mechanical ventilation (OR, 2.9; 95% CI, 1.4 - 5.9; p = 0.003), blood transfusion (OR, 1.23; 95% CI, 1.03 - 1.49; p = 0.02), and thrombocytopenia (OR, 0.72; 95% CI, 0.60 - 0.87; p < 0.001). Conclusion: Values of these independent variables should be taken into account when performing longitudinal screening for ROP.